Pearls and pitfalls: Electrophysiology for primary headaches. (June 2013) - Magis, Delphine; Vigano, Alessandro; Sava, Simona; d'Elia, Tullia Sasso; Schoenen, Jean; Coppola, Gianluca
Background: Primary headaches are functional neurological diseases characterized by a dynamic cyclic pattern over time (ictal/pre-/interictal). Electrophysiological recordings can non-invasively assess the activity of an underlying nervous structure or measure its response to various stimuli, and are therefore particularly appropriate for the study of primary headaches. Their interest, however, is chiefly pathophysiological, as interindividual, and to some extent intraindividual, variations preclude their use as diagnostic tools. Aim of the work: This article will review the most important findings of electrophysiological studies in primary headache pathophysiology, especially migraine on which numerous studies have been published. Results: In migraine, the most reproducible hallmark is the interictal lack of neuronal habituation to the repetition of various types of sensory stimulations. The mechanism subtending this phenomenon remains uncertain, but it could be the consequence of a thalamocortical dysrythmia that results in a reduced cortical preactivation level. In tension-type headache as well as in cluster headache, there seems to be an impairment of central pain-controlling mechanisms but the studies are scarce and their outcomes are contradictory. The discrepancies between studies might be as a result of methodological differences as well as patients' dissimilarities, which are also discussed. Conclusions and perspectives: Electrophysiology is complementary to functional neuroimaging and will undoubtedly remain an important tool in headache research. One of its upcoming applications is to help select neurostimulation techniques and protocols that correct best the functional abnormalities detectable in certain headache disorders.